ANALISIS POTENSI SEKTOR PERTANIAN, KEHUTANAN DAN PERIKANAN DI DAERAH KABUPATEN/KOTA KEPULAUAN DI BAGIAN BARAT SUMATERA - Ya’aman Telaumbanua; M. Sya’fii; Sirojuzilam Sirojuzilam (Jurnal Ilmiah Global Education, 2023)
This study aims to analyze the potential of the agricultural, forestry and fisheries sectors in six regencies and one city in the western part of Sumatra, namely; Simeulue District, Aceh Province, Nias, South Nias, North Nias, West Nias and Gunungsitoli City in North Sumatra Province and Mentawai Islands District in West Sumatra Province. The analytical method used is through Location Quotient (LQ) Analysis, Dynamic Location Quotient (DLQ) and Kalssen Typology Analysis during the 2008-2022 period. The results of the LQ calculation show that the agriculture, forestry and fisheries sectors are the basic or leading sectors in Simeulue, Nias, South Nias, North Nias, West Nias and Mentawai Islands, while this sector in Gunungsitoli City is a non-base sector. Based on the results of the DLQ analysis, although this sector is the base sector in Nias, North Nias, West Nias and the Mentawai Islands, in the long term/time period 2008-2022 the growth rate of this sector tends to slow down markedly by a DLQ value < 1. In Nias Regency, even during a period of 15 years, only once in 2013 did it show a DLQ value > 1 or a fast growth rate, besides that it experienced a slow rate. In contrast to the results of the analysis in Simeulue and South Nias Regencies, where during the period 2008-2022 this base sector was consistent with growth rates that tended to be fast. While the results of the Klassen Typology analysis show that the agricultural, forestry and fisheries sectors in South Nias and Mentawai Islands are developed sectors, in Simeulue, Nias, North Nias and West Nias Regencies are developing sectors, namely the advanced but depressed sector, while in Gunungsitoli City it is sectors that have the potential to be developed into advanced sectors.